Unusual seeding effect in the liquid-assisted high-pressure polymorphism of chlorpropamide. Issue 29 (16th June 2016) - Zakharov, B. A.; Goryainov, S. V.; Boldyreva, E. V.
Abstract : When crystals of four polymorphs – a stable α-form and three metastable ones (β-, γ-, δ-forms) – are simultaneously present in a pressure cell, immersed in a 1 : 1 pentane–isopentane mixture, the least stable β-form recrystallises exclusively into the γ-form (if no δ-form seed is present) or concomitantly into the γ- and δ-forms (if a seed of the δ-form is present). Abstract : When crystals of four polymorphs – a stable α-form and three metastable ones (β-, γ-, δ-forms) – are simultaneously present in a pressure cell, immersed in a 1 : 1 pentane–isopentane mixture, the least stable β-form recrystallises exclusively into the γ-form (if no δ-form seed is present) or concomitantly into the γ- and δ-forms (if a seed of the δ-form is present). However, the β-form never recrystallises to the stable α-form, even if the latter is also present as a potential seed.